2021
DOI: 10.1186/s13046-021-02029-y
|View full text |Cite
|
Sign up to set email alerts
|

EIF4A3-induced circ_0084615 contributes to the progression of colorectal cancer via miR-599/ONECUT2 pathway

Abstract: Background Colorectal cancer (CRC) is a common malignant tumor. Circular RNAs (circRNAs) have been reported to take part in the progression of CRC. However, the functions of circ_0084615 in CRC development are still undefined. In this study, we aimed to explore the functions and underlying mechanisms of circ_0084615 in CRC. Methods qRT-PCR, western blot assay and IHC assay were utilized for the levels of circ_0084615, miR-599, ONECUT2 or EIF4A3. 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…7A ). Previous studies have proved that EIF4A3, a core component of the exon junction complex, play an essential role in pre-mRNA splicing and could induce circular RNA formation via binding to the upstream region of some particular mRNAs 20 . Therefore, we conduced RIP assay using anti-EIF4A3 antibody and confirmed the enrichment of PRKCI mRNA in EIF4A3 precipitates compared with the negative control (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7A ). Previous studies have proved that EIF4A3, a core component of the exon junction complex, play an essential role in pre-mRNA splicing and could induce circular RNA formation via binding to the upstream region of some particular mRNAs 20 . Therefore, we conduced RIP assay using anti-EIF4A3 antibody and confirmed the enrichment of PRKCI mRNA in EIF4A3 precipitates compared with the negative control (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Aberrant expression of circRNAs plays a crucial role in the development of many cancers (25)(26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies described novel ONECUT2 regulatory mechanisms. In CRC, circular RNA (circ_0084615) serves as a sponge for miR-599, which directly binds to ONECUT2 [ 54 ]. Furthermore, studies on CRC cells showed that by silencing circ_0084615, EMT-related markers ZEB2 and vimentin are reduced and E-cadherin is elevated.…”
Section: Discussionmentioning
confidence: 99%